The Effect of Learning Styles and Motivation on Students’ Vocabulary Acquisition: The Case of Second Year LMD Students of English at the University of Constantine1 - BELLOUT, Hadjer (Journal of Human Sciences, 2014)
This research aims at establishing the importance of learning styles and motivation in second language acquisition and their effect on vocabulary acquisition as a key aspect of developing proficiency in a second language. The educational setting in which this study takes place is the Department of Foreign Languages, Faculty of Letters and English Language, University of Constantine1. The underlying hypotheses is that if teachers focus on the learners’ learning styles and attempt to raise their motivation, this may help them for better vocabulary acquisition. The study consisted of administering a pre-test and a post test to control and experimental groups; a treatment of vocabulary activities was given to the experimental group. The tested sample is randomly selected from second year students of English (LMD) population. The results confirm the hypothesis and show that the learners learn nearly all the new words when teachers focus on their learning styles and raise their consciousness about how to use them and attempt to enhance their motivation while accomplishing the tasks. Some pedagogical suggestions are made for a more effective way to learn vocabulary and help teachers in their teaching through creating a motivating environment and matching their teaching methods with their learners’ styles.